Sustainable Legal Protection of the Environment and Public Health Against the Threat of Industrial Liquid Waste - Mellal, Abdelhammid (Journal of Legal Studies and Researches, 2024)
The objective of this study is to demonstrate the way in which liquid industrial waste is managed through the adoption of green industry policy based on legal techniques and mechanisms, most notably industrial wastewater treatment and recycling plants, as an effective mechanism for environmental protection and public health, in order to enhance the dimensions of sustainable development.